Introduction to digital electronics - Lo, Arthur Wu-nien (Addison-Wesley Pub. Co., 1967)
The purpose of this book is to serve as an introduction to the digital operation of solid-state electronic devices and circuits essential to digital information processing systems. It is written for advanced undergraduates and beginning graduate students, and for practicing engineers who are newly entering the field. The treatment presumes that the reader is familiar with generals physics and mathrmatics, and the bacsic principles of electronic circuits.